Design and In-vitro Evaluation of Controlled Release Cephalexin Subgingival Films Using Natural Biodegradable Polymer - Chandu Babu Rao, Soad Ali Mohammed; Turkiya Omer Alokbe, Bahlul Z. Awen, Prakash Katakam* (Recent Research in Science and Technology, 2010)
The aim of the present investigation was to prepare and evaluate cephalexin controlled release subgingival films using biodegradable sodium alginate. The equipment necessary for the present investigation was fabricated and employed for casting of sodium alginate subgingival films. Subgingival films of drug:polymer in various proportions (10:90, 25:75, 50:50 and 75:25) were prepared using solvent casting method. A 10%w/v CaCl2 solution was used for gelation of the films. As polymer concentration is increased the smoothness of the films increased. The thickness of films varied from 146±5 to 312±15 μm which is well below the recommended thickness (<300 μm) of the subgingival films. The average weight of the films was found to be between 14.21±0.18 and 20.42 ±0.49. The percentage of drug content ranged from 53.14 to 56.81%. The low values may be due to loss of drug during treatment of the films with CaCl2 solution. In vitro release studies of all the films showed an initial burst release for the first 24 hrs, followed by controlled release of cephalexin (>0.24 μg/ml) up to 120 hrs which is sufficient to inhibit the growth of the micro-organisms. The rate of drug release was inversely proportional to polymer concentration in the formulations. The low K1 and ‘r’ values obtained may be due to biphasic drug release pattern. The formulations did not fit into Higuchi equation because of low values of <0.788025 which indicate that the drug release might be due to diffusion only in second phase of dissolution. All the films have shown to have integrity even after 5 days of dissolution studies. The formulations C1 and C2 which contain 90 and 75%w/w of polymer could be employed for controlled delivery of cephalexin for 5 days in subgingival infections. Sodium alginate, being a biodegradable polymer is a good choice as drug carrier in the present study.